2012
DOI: 10.1152/ajprenal.00397.2011
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct-specific knockout of adenylyl cyclase type VI causes a urinary concentration defect in mice

Abstract: Collecting duct (CD) adenylyl cyclase VI (AC6) has been implicated in arginine vasopressin (AVP)-stimulated renal water reabsorption. To evaluate the role of CD-derived AC6 in regulating water homeostasis, mice were generated with CD-specific knockout (KO) of AC6 using the Cre/loxP system. CD AC6 KO and controls were studied under normal water intake, chronically water loaded, or water deprived; all of these conditions were repeated in the presence of continuous administration of 1-desamino-8-d-arginine vasopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 24 publications
(30 reference statements)
3
61
1
Order By: Relevance
“…11 Two mouse lines were used: (1) mice containing a transgene expressing Cre recombinase under the control of AQP2-Cre that express Cre selectively in renal collecting duct principal cells and (2) were bred to be doubly homozygous for the floxed Pkd1 and ADCY6 genes (the latter as previously reported 12 ). These mice were crossed with AQP2-Cre mice through a series of breedings to obtain mice that were homozygous for the floxed Pkd1 gene, heterozygous for AQP2-Cre, and either homozygous or heterozygous for the floxed ADCY6 gene.…”
Section: Transgenic Mouse Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Two mouse lines were used: (1) mice containing a transgene expressing Cre recombinase under the control of AQP2-Cre that express Cre selectively in renal collecting duct principal cells and (2) were bred to be doubly homozygous for the floxed Pkd1 and ADCY6 genes (the latter as previously reported 12 ). These mice were crossed with AQP2-Cre mice through a series of breedings to obtain mice that were homozygous for the floxed Pkd1 gene, heterozygous for AQP2-Cre, and either homozygous or heterozygous for the floxed ADCY6 gene.…”
Section: Transgenic Mouse Linesmentioning
confidence: 99%
“…For example, CD AC6 deficiency prevents AVP-stimulated epithelial Na channel activity in the CD 15 ; however, CD water reabsorption is only mildly impaired by CD AC6 absence. 12 Although these studies were conducted under different conditions (epithelial Na channel activity was studied in vitro, and water reabsorption was studied in vivo), they raise the possibility that AVP might exert different effects on the CD depending on which adenylyl cyclase isoforms are activated. It would seem most likely that AVP binding per se is not the determinant of which adenylyl cyclase isoforms are activated, but rather, other cellular modulatory systems are involved.…”
mentioning
confidence: 99%
“…25 Functional studies have shown a role of AC6 in the thick ascending limb, distal tubule, and collecting duct insofar as mice lacking AC6 have Bartter syndrome 26 and nephrogenic diabetes insipidus (NDI). 27,28 In a collecting duct-specific AC6 knockdown model, vasopressin-stimulated epithelial sodium channel open probability was abolished. 29 Based on studies indicating that vasopressin V 2 receptors use the AC6-cAMP signaling pathway [26][27][28][29][30] and the relatively high abundance of AC6 in the proximal tubule, 23,30,31 we proposed that AC6 may contribute to PTH-stimulated cAMP formation, P i excretion, and thus, P i homeostasis.…”
mentioning
confidence: 99%
“…AC6 is inhibited by Ca 2+ at the micromolar level (Cooper et al, 1994) and is relatively abundant in collecting duct principal cells (Chabardes et al, 1996;Helies-Toussaint et al, 2000). Although both AC3 (also known as ADCY3) and AC6 are expressed in principal cells and have both been suggested to contribute to the overall rise in cAMP during vasopressin stimulation (Hoffert et al, 2005), the relevance of AC6 as a major enzyme in modulating the vasopressin-regulated water reabsorption is supported by the observation that collecting-duct-specific knockout of AC6 causes a urinary concentration defect associated with reduced vasopressinstimulated cAMP accumulation (Roos et al, 2012). Taken together, our results indicate that the reduction in cAMP accumulation upon simultaneous stimulation with forskolin and activation of CaSR results from impairment of cAMP synthesis that is likely due to the inhibition of AC6 activity as a consequence of intracellular Ca 2+ rise.…”
Section: Discussionmentioning
confidence: 99%